Optimalisasi Koordinator Sumber Daya Air Wilayah Glenmore Dalam Pelayanan Pengelolaan Irigasi Di Wilayah Tegalsari Kabupaten Banyuwangi - Eka Radyta Budiyanti; Sri Wilujen; Herwin Kurniadi (Journal on Education, 2024)
This research aims to determine the optimization of irrigation management services carried out by the Water Resources Coordinator for the Glenmore region through the regional interpreter with HIPPA for the Tegalsari region. Research conducted at the Glenmore regional Water Resources Coordinator used a qualitative descriptive approach. The data collection techniques used were direct observation, in-depth interviews and secondary sources (documents, theses, journals). From the survey that has been carried out, the research results show that irrigation management services in the Tegalsari area carried out by Juru together with HIPPA in the Tegalsari area are less than optimal. The Tegalsari area is included in the work area of ​​the Glenmore regional air resources coordinator which is in the downstream area and has quite extensive raw rice fields but the water supply in the area is inadequate, causing a shortage in air demand. Apart from that, the results of this research found that the large area of ​​Tegalsari causes irrigation management services to be not optimal, and the distribution of water discharge in farmers' fields is not timely. In conditions like this it is very important to manage air sources and irrigation water distribution systems. KORSDA through the HIPPA joint interpreter and farmers in the Tegalsari area need to hold regular meetings for socialization and coordination regarding irrigation management and drawing up plans for the distribution of needed irrigation water. The water mill system is one way to distribute irrigation water.